The manifestly evident environmental improvement: optimistic look at a figure that is currently unfriendly - Ruesta Otoya, Favio (2022)
In 2013, the Agency for Environmental Assessment and Enforcement introduced the manifestly evident environmental improvement to the legal system. This figure had a negative reception as it seemed to delegitimize the obligations established in the environmental certification, the most important environmental license in Peru.This paper analyses the questions born with the creation of the manifestly evident environmental improvement and the effective use of this figure by the public.